Delayed hospital discharges of older patients: a systematic review on prevalence and costs - Landeiro, F; Roberts, K; Gray, A; Leal, J (Oxford University Press, 2017)
Purpose of the Study: To determine the prevalence of delayed discharges of elderly inpatients and associated costs. Design and Methods: We searched Medline, Embase, Global Health, CAB Abstracts, Econlit, Web of Knowledge, EBSCO - CINAHL, The Cochrane Library, Health Management Information Consortium, and SCIE - Social Care Online for evidence published between 1990 and 2015 on number of days or proportion of delayed discharges for elderly inpatients in acute hospitals. Descriptive and regression analyses were conducted. Data on proportions of delayed discharges were pooled using a random effects logistic model and the association of relevant factors was assessed. Mean costs of delayed discharge were calculated in USD adjusted for Purchasing Power Parity (PPP). Results: Of 64 studies included, 52 (81.3%) reported delayed discharges as proportions of total hospital stay and 9 (14.1%) estimated the respective costs for these delays. Proportions of delayed discharges varied widely, from 1.6% to 91.3% with a weighted mean of 22.8%. This variation was also seen in studies from the same country, for example, in the United Kingdom, they ranged between 1.6% and 60.0%. No factor was found to be significantly associated with delays. The mean costs of delayed discharge also varied widely (between 142 and 31,935 USD PPP adjusted), reflecting the variability in mean days of delay per patient. Implications: Delayed discharges occur in most countries and the associated costs are significant. However, the variability in prevalence of delayed discharges and available data on costs limit our knowledge of the full impact of delayed discharges. A standardization of methods is necessary to allow comparisons to be made, and additional studies are required-preferably by disease area-to determine the postdischarge needs of specific patient groups and the estimated costs of delays.